Prospective randomized controlled trial comparing the functional outcome of olecranon osteotomy versus triceps tongue elevation for surgical exposure of distal humerus in adults - Rajak, Asish; Maharjan, Rajiv; Shrestha, Bikram Prasad; Chaudhary, Pashupati; Kalawar, Rosan PS (Journal of Kathmandu Medical College, 2018)
Background: Fractures of the distal end of the humerus are difficult to treat. The goal of treatment is to achieve a stable, painless elbow with early adequate range of motion. They are operated mainly by posterior approach among which olecranon osteotomy (bony component violation) and triceps tongue elevation (soft tissue component breach) were used in this study. Objectives: The aim of this study was to compare olecranon osteotomy and triceps tongue elevation in terms of functional outcome (Mayo elbow performance index), rates of complications and others. Methodology: A randomized control trial was conducted including 39 eligible adults (20 in triceps tongue elevation and 19 in olecranon osteotomy group) presenting to B.P. Koirala Institute of Health Sciences during the study period of 12 months duration. All skeletally mature adult patients with isolated traumatic closed intra-articular or distal end fracture of humerus without distal neurovascular deficit were included. Patients with polytrauma, refractures, compartment syndrome and patient not giving consent were excluded from the study. They were operated and followed up at 2, 6, 12 and 24 weeks. Results: The demographic profiles of the two groups were comparable. There was significant difference between the intraoperative time between the two groups (p=0.009). At final follow up, there were no significant differences in functional outcome and complications. Conclusion: The approaches are comparable in terms of union, post-operative function and complications. There was increased intraoperative time in the olecranon osteotomy approach suggesting that patients who cannot tolerate longer intraoperative time may benefit from triceps tongue elevation approach.